Trace metal levels in the sediment and water of river Bhadra, Karnataka, India - S.THIRUMALA,; T.R.SHASHI SHEKAR,; B.R. KIRAN, (International Journal of Pharma and Bio Sciences, 2019)
The main objective of the present study is to know the trace metal levels in the water and sediments samples of river Bhadra, Karnataka. Availability of trace metals in the environment markedly influences their effect on higher plant organisms. Measurements of the total metal concentration in soil or sediment are therefore unlikely to reflect the amount of metal actually available to the biota. Bhadra river sediments collected between April 2010 and May 2011 were analysed for Iron (Fe), Zinc (Zn), Copper (Cu), Lead (Pb), Nickel (Ni), Cobalt (Co) and Cadmium (Cd) in the less than 50-63 µm grain size fraction. These trace metals were analysed by using an atomic absorption spectrophotometer with appropriate standards and several blanks prepared similar to the samples. The river sediments were characterised by a sandy to a very fine texture. There were no significant longitudinal differences in all the elements apart from sediment Pb and Zn contents. River Bhadra was considered polluted with respect to Pb and Cd, which were comparatively higher than unpolluted sediments and geochemical background values. This backings comparative outcome on surface water follows component levels. The greater parts of the locales of the waterway channel a zone of moderately comparable lithological qualities. In this way, aside from the immediate waste contribution to waterway from civil and modern sources, absences of explicit point sources demonstrate lithological metal roots with limited varieties. A final comparative evaluation of the river water and sediments trace metal pollution was made from the study results. The data is vital for pollution management of the river as information about metal loadings into the river system is lacking.